Hepatic pedicle endometriosis: Case report and review of the literature. Issue 10 (31st July 2019) - Eychenne, Camille; Suc, Bertrand; Delchier, Marie C.; Vidal, Fabien; Rimailho, Jacques; Illac, Claire; Breibach, Florence; Vaysse, Charlotte; Chantalat, Elodie
Abstract: The localization of endometriotic disease in the hepatic pedicle has never been reported to date. We report the first case of a 67‐year‐old postmenopausal patient having presented an endometriotic lesion in the hepatic pedicle. A surgical biopsy was needed to confirm the diagnosis after a first radiologic biopsy that concluded the presence of a mucinous cystic tumor with low‐grade dysplasia. Medical treatment with aromatase inhibitors was carried out because of the inextirpable nature of the lesion. The diagnosis and therapeutic management of this rarely occurring lesion of atypical localization in a postmenopausal patient is presented here. A review of the literature on this localization could have led to a damaging surgical treatment due to the different diagnoses suggested. Management of endometriosis relies on a multidisciplinary approach that each practitioner must know how to broach with patients of all ages.